Police epistemic culture and boundary work with judicial authorities and forensic scientists: the case of transnational DNA data exchange in the EU - Machado, Helena (2019)
The exchange of forensic DNA data is seen as an increasingly important tool in criminal investigations into organised crime, control strategies and counterterrorism measures. On the basis of a set of interviews with police professionals involved in the transnational exchange of DNA data between EU countries, this paper examines how forensic DNA evidence is given meaning within the various different ways of constructing a police epistemic culture, it is, a set of shared values concerning valid knowledge and practices normatively considered adequate and legitimate. The police epistemic culture is fuelled by multiple dynamics of boundary work, revealing how police professionals involved in international cooperation (i) define their specific core activities and competencies; (ii) construct particular understandings of valid knowledge and how it should be produced; (iii) enact the police epistemic culture in contrast to the epistemic cultures of the judicial authorities and forensic scientists.